Colorectal adenocarcinoma in pregnancy: intraoperative finding in a patient with intestinal obstruction - R., Carla M. Cruz; T., Carlos E. Pérez; S., Axel A. Núñez; G., Perla González; Rocha, Gadiel A. C.; González, Jaime (International Surgery Journal, 2024)
Colorectal cancer, a common malignancy with significant morbidity and mortality, is infrequently encountered during pregnancy. This rare overlap of conditions creates a formidable diagnostic. The therapeutic approach is equally complex, involving difficult decisions on whether to delay treatment until after delivery or to pursue immediate intervention, all while considering the impact on both maternal and fetal health. This case highlights the need for heightened awareness among clinicians, as well as the development of clear protocols to guide the management of colorectal cancer in pregnant patients. In the current case report we describe and document the incidental intraoperative findings of a colorectal adenocarcinoma in a 27-year-old patient with 20 weeks of pregnancy presenting with clinical symptoms of intestinal obstruction. We present the difficult diagnostic and therapeutic approach involving the decision on the treatment of an acute pathology as is intestinal obstruction. As well as to assess whether or not to start systemic oncological therapy and whether or not to end the pregnancy.